Strategi pengembangan sumber daya manusia berbasis kompentensi dalam meningkatkan kinerja pegawai di Universitas Jambi - Hendriyaldi Hendriyaldi; Ovie Yanti (Jurnal Paradigma Ekonomika, 2021)
This study aims to analyze the implementation of competency-based Human resources (HR) development strategies in improving employee performance at Jambi University. This research is descriptive using a qualitative approach. Data collection techniques include observation, interviews, and documentation. The results show that the HR development strategy and competency standards in improving employee performance at the University of Jambi are guided by the Main Performance Indicators of State Universities IKU-PTN and the Jambi University Strategic Plan 2021-2024. This strategy has improved the competence of lecturers and education staff.